Analisis Harga Saham, Volume Perdagangan Saham, Terhadap Keputusan Stock Split dan Reverse Split PT. Astra Internasional Tbk dan PT. Smartfren Telecom Tbk - Achmad, Daniel Noor; M, Bintang Sahala; Olive, Gabriella (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
This research is aimed at analyzing the stock price, trading volume and the financial performance of the company and how these variables influence the management's decision for stock split and reverse split. Stock price is the variable used to create the profile of expected retum to value the risk ofthe stock that company will give to the owner ofthe company, and trading volume is used to analyse the liquidity of the investment instrumenst, and lastly to examine the success of the corporate action using the financial performance as the indicator of Eaming Per Share (EPS). Analytical method is used to analyze the coworate action of PT. Astra Internasional Tbk in making the stock split decision with the ratio 1:10 in 5 june 2012. Soon after, PT. Smartfren Telecom made the decision to reverse split by 20:1 in 15 february 2012. This study will discuss the stock perfomance and the financial performance before and after the decision by both companies. Keyword: Stock Price, Trading Volume Acivity (TVA), Earning Per Share (EPS), Price Earning Ratio (PER)